IMPLEMENTATION OF KURIKULUM MERDEKA IN MATHEMATICS CLASS IV DEMANGAN 1 BANGKALAN ELEMENTARY SCHOOL - Ana Naimatul Jannah; Nurul Imaniyah; Irvania Emiliawati; Dela Lorensya Putri (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Its position as the parent and underlies various other disciplines makes mathematics a very important subject to study, including at the elementary school level. In other conditions, there is a new curriculum that has been implemented by the government, namely the independent curriculum. The purpose of this study is to determine the implementation of the independent curriculum in mathematics. at UPTD SDN Demangan 1 Bangkalan. The type of research used is descriptive qualitative, namely describing the implementation of the independent curriculum in class IV mathematics. The subjects studied were students of class IV. Forms of data collection techniques used in the form of observation, interviews, and documentation. The results of the research show that the implementation of the independent learning curriculum in mathematics learning has not been able to get rid of students' negative thinking in mathematics. Some of the factors that cause this are inappropriate learning methods, lack of use of learning media, and the inaccurate application of independent learning for students. Based on the results of the research above, it can be concluded that the implementation of the independent curriculum in mathematics at SDN Demangan 1 Bangkalan has not obtained optimal results